Human Milk and Allergic Diseases: An Unsolved Puzzle - Munblit, Daniel; Peroni, Diego; Boix-Amorós, Alba; Hsu, Peter; Land, Belinda; Gay, Melvin; Kolotilina, Anastasia; Skevaki, Chrysanthi; Boyle, Robert; Collado, Maria; Garssen, Johan; Geddes, Donna; et al. (Nutrients, 2017)
There is conflicting evidence on the protective role of breastfeeding in relation to the development of allergic sensitisation and allergic disease. Studies vary in methodology and definition of outcomes, which lead to considerable heterogeneity. Human milk composition varies both within and between individuals, which may partially explain conflicting data. It is known that human milk composition is very complex and contains variable levels of immune active molecules, oligosaccharides, metabolites, vitamins and other nutrients and microbial content. Existing evidence suggests that modulation of human breast milk composition has potential for preventing allergic diseases in early life. In this review, we discuss associations between breastfeeding/human milk composition and allergy development.